3(2+x)=-36

Simple and best practice solution for 3(2+x)=-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(2+x)=-36 equation:


Simplifying
3(2 + x) = -36
(2 * 3 + x * 3) = -36
(6 + 3x) = -36

Solving
6 + 3x = -36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 3x = -36 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = -36 + -6
3x = -36 + -6

Combine like terms: -36 + -6 = -42
3x = -42

Divide each side by '3'.
x = -14

Simplifying
x = -14

See similar equations:

| x^2-2400=0 | | -2g-6=-9 | | 360=(6+3w)(w) | | 18+0.5x=25 | | 3(2c-5)+2c= | | -8w-2=-10-4w | | 4x+6-x=22+6 | | -1/3(9s-36t=-5)= | | 24+2X=110 | | -5+3y=-6 | | 5p-2q=3m+d | | -7(x+2y+5z)= | | 11a+b=5a+24 | | 8y=-8+7y | | -10+3y=-6 | | 64-x=156 | | y+1=16-2y+6 | | 5x-3=13+2x | | 10/75=18/n | | -2y+18=4(y+3) | | (K^1/10)^-2/(k^9)^1/5 | | 55=4(2y-3) | | P=20log(146*2300) | | 1-2j=10-3j | | 5(y+8)-8y=25 | | -6=-5/6v | | 8x+2x-3y-9x= | | -2w-3(3x+4w)+2x= | | 2(v-5)-5v=-28 | | 2X+110=200 | | 11a+b=5a-24 | | 1a+b=5a-24 |

Equations solver categories